Dekadensi Motivasi Tenaga Pendidik Senior dan Implikasinya terhadap Kultur Kerja Kolaboratif di Pesantren - M. Fakhroni Hamzah; M. Naufal Al Qurthuby Fuady S. (Visionaria: Journal of Educational Innovation Management, 2025)
The decline in motivation among senior teachers has become a structural challenge for Islamic boarding schools, particularly in relation to sustaining a collaborative work culture. This study aims to identify the factors contributing to motivational decline, analyze its implications for organizational collaboration, and formulate strategies to strengthen the role of senior teachers in pesantren. Using a descriptive qualitative approach, data were obtained through in-depth interviews, participant observation, and document analysis involving senior teachers, junior teachers, and institutional leaders at Nurul Jadid Islamic Boarding Schools. The data were processed through thematic reduction, categorization, and triangulation techniques to ensure validity. The findings indicate that motivational decline is primarily driven by job fatigue, limited institutional recognition, and intergenerational gaps, which collectively reduce senior teachers’ engagement in collaborative activities. This condition affects the effectiveness of knowledge transfer, team synergy, and innovation within the institution. The novelty of this study lies in linking motivational decline with the fragmentation of collaborative work culture in pesantren settings. The study recommends managerial strategies such as structured recognition, adaptive capacity-building, and the recontextualization of senior teachers’ roles to maintain organizational continuity and support a more sustainable collaborative environment.